2022
DOI: 10.1002/bdr2.2060
|View full text |Cite
|
Sign up to set email alerts
|

In‐utero cannabis exposure and long‐term psychiatric and neurodevelopmental outcomes: The limitations of existing literature and recommendations for future research

Abstract: Given increases in cannabis use in pregnancy and animal model researchshowing effects of in-utero cannabis exposure, high-quality information on long-term consequences of in-utero cannabis exposure in humans is needed. While reviews have summarized findings from observational studies with humans, reviews have not focused on limitations of these studies and recommendations for future research. Therefore, we critically reviewed observational research on in-utero cannabis exposure and psychiatric and neurodevelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…There were several limitations of the included studies that may have contributed to the mixed findings on in utero cannabis exposure and birth defects. These limitations are similar to those of studies on in utero cannabis exposure and other outcomes, such as long-term neurodevelopmental and psychiatric problems (15). First, many of the studies had samples that were relatively small (e.g., 6 of the 20 studies had samples under 500) and reported findings with wide confidence intervals.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…There were several limitations of the included studies that may have contributed to the mixed findings on in utero cannabis exposure and birth defects. These limitations are similar to those of studies on in utero cannabis exposure and other outcomes, such as long-term neurodevelopmental and psychiatric problems (15). First, many of the studies had samples that were relatively small (e.g., 6 of the 20 studies had samples under 500) and reported findings with wide confidence intervals.…”
Section: Discussionmentioning
confidence: 71%
“…The causes and risk factors for many structural birth defects remains unknown, and understanding preventable causes and risk factors for structural birth defects is particularly important given the strong association between birth defects and morbidity/mortality ( 16 ). Given this need, we conducted a systematic review using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to evaluate whether in utero cannabis exposure is associated with structural birth defects compared to pregnancies with no cannabis exposure (Prospective Register of Systematic Reviews [PROSPERO] registration number: CRD42022308130; ( 17 )].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is critical to note that cannabis use during pregnancy is associated with adverse perinatal outcomes, including low offspring birth weight and pre‐term delivery [ 46 , 47 ], and may increase risk for offspring psychopathology in childhood, including externalizing, attention, thought and social problems [ 48 ]. Because of concerns regarding these health risks, national organizations recommend that pregnant women abstain from prenatal cannabis use [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limitations to the conclusiveness of the current body of evidence ( 19 ). Limitations of current evidence include sample size and generalizability, self-reported data, lack of data on timing and dosing of cannabis ingestion, as well as a lack of focus on social environmental contexts influencing use of cannabis during pregnancy ( 20 , 21 ). The extant data has identified that more research is needed on maternal cannabis use to optimize public health promotion and intervention development ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%